2015
DOI: 10.1371/journal.pone.0118304
|View full text |Cite
|
Sign up to set email alerts
|

Findings from Integrated Behavioral and Biologic Survey among Males Who Inject Drugs (MWID) — Vietnam, 2009–2010: Evidence of the Need for an Integrated Response to HIV, Hepatitis B Virus, and Hepatitis C Virus

Abstract: IntroductionGiven the overlapping modes of transmission of HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV), understanding the burden and relationship of these infections is critical for an effective response. Representative data on these infections among males who inject drugs (MWID), the key high-risk population for HIV in Vietnam, are currently lacking.MethodsData and stored specimens from Vietnam’s 2009-2010 Integrated Biologic and Behavioral Survey, a cross-sectional study among high-risk populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(37 reference statements)
1
18
1
Order By: Relevance
“…A detailed description of the methodology has been described previously 9. Briefly, a representative sample of MSM was surveyed during September 2009–February 2010 for HIV infection along with associated risk behaviours (eg, condom use, needle-sharing) and exposure to HIV/AIDS prevention and care services.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the methodology has been described previously 9. Briefly, a representative sample of MSM was surveyed during September 2009–February 2010 for HIV infection along with associated risk behaviours (eg, condom use, needle-sharing) and exposure to HIV/AIDS prevention and care services.…”
Section: Methodsmentioning
confidence: 99%
“…Much of this burden is attributed to the estimated 8%–12% population prevalence of hepatitis B virus (HBV) and up to 26.7% of liver cancer attributed to HCV infection 7 8. Higher rates of HCV and HBV infection are reported among PWID and people living with HIV (PLHIV) 7 9. In one study, an estimated 39.6% (95% CI 34.8% to 44.3%) of those PLHIV receiving HIV treatment tested anti-HCV+ 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis C virus (HCV) infection prevalence is lower, estimated at 0.5-4% [2,3,6]. However, higher HBV and HCV infection prevalences are reported among people living with HIV (PLHIV) and at risk for HIV in Vietnam, ascribed to overlapping behavioral risks for HIV, HBV and HCV exposures [3,7,8]. In a study among people who inject drugs (PWID) in northern Vietnam, prevalence of HIV was 42.4%; of hepatitis B core antibody (HBc Ab), 80.9%; and of antibody to HCV (anti-HCV), 74.1% [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study among people who inject drugs (PWID) in northern Vietnam, prevalence of HIV was 42.4%; of hepatitis B core antibody (HBc Ab), 80.9%; and of antibody to HCV (anti-HCV), 74.1% [8]. The 2009-2010 surveillance data among male PWID in 10 Vietnam provinces found HBsAg-positive prevalence of 12% to 28% across provinces and combined HCV antigen/antibody prevalence of 11% to 87%; HCV antigen/antibody prevalence was higher among HIV-positive (95.8%) compared with HIV-negative male PWID (52.2%) [7]. Previous studies have reported that HBV and HCV co-infections among PLHIV are associated with increased hepatic disease and overall morbidity and mortality [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%